2013
DOI: 10.1016/j.kjms.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Eugenosedin‐A ameliorates hyperlipidemia‐induced vascular endothelial dysfunction via inhibition of α1‐adrenoceptor/5‐HT activity and NADPH oxidase expression

Abstract: Eugenosedin-A (Eu-A) effects on vascular endothelial dysfunction and oxidative stress in a hyperlipidemic rat model were investigated. Rats were randomly divided into four groups: two control groups and two treatment groups. The control rats received a regular diet or high fat diet (HFD); the treatment rats fed received an HFD with 5 mg/kg Eu-A or atorvastatin for 10 weeks. No changes in serotonin levels were observed in the four groups; norepinephrine levels were enhanced in the HFD group which was attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…As with other metabolic factors, such as hyperglycemia and hHcys, oxidative stress is proved to contribute to the deleterious effects of hyperlipidemia on renal injury. In high-fat diet fed mice, the expression of NADPH oxidase subunits, including p47phox, Nox2, and p67phox, was significantly upregulated, and the inhibitor could ameliorate hyperlipidemia-induced endothelial dysfunction via inhibition of NADPH oxidase expression [82]. However, in the study of Scheuer et al, it is reported that xanthine oxidoreductase rather than NADPH oxidase mainly accounted for the generation of ROS in glomeruli and tubulointerstitium induced by hyperlipidemia [83].…”
Section: Nadph Oxidase and Hyperlipidemia-associated Glomerular Inmentioning
confidence: 99%
“…As with other metabolic factors, such as hyperglycemia and hHcys, oxidative stress is proved to contribute to the deleterious effects of hyperlipidemia on renal injury. In high-fat diet fed mice, the expression of NADPH oxidase subunits, including p47phox, Nox2, and p67phox, was significantly upregulated, and the inhibitor could ameliorate hyperlipidemia-induced endothelial dysfunction via inhibition of NADPH oxidase expression [82]. However, in the study of Scheuer et al, it is reported that xanthine oxidoreductase rather than NADPH oxidase mainly accounted for the generation of ROS in glomeruli and tubulointerstitium induced by hyperlipidemia [83].…”
Section: Nadph Oxidase and Hyperlipidemia-associated Glomerular Inmentioning
confidence: 99%
“…Experimental studies and clinical trials have shown that reduced numbers and impaired functional capacity of EPCs occurred in patients with hypercholesterolemia or in cell culture with ox-LDL, whereas high-density lipoprotein cholesterol could be atheroprotective by increasing EPC numbers. 61 In a hypercholesteremic murine model of atherosclerosis, Kinkade et al 60 have recently identified NOX as the primary source of ROS in atherosclerotic lesions. The production of ROS is significantly increased in patients with hyperlipidemia.…”
Section: Nox-mediated Endothelial and Epc Dysfunction In Hyperlipidemiamentioning
confidence: 99%
“…Eu‐A reduced obesity‐related hyperglycemia, hyperinsulinemia, hyperlipidemia [13], inflammation, and adhesion molecules [14–16]. Eu‐A also inhibited high‐fat diet (HFD)‐induced vascular and endothelial dysfunction and oxidative stress by attenuating α 1‐ adrenoceptor/5‐HT activity and NADPH oxidase [16]. Based on our findings, Eu‐A could be used to control the HFD‐induced metabolic syndrome, which is associated with an increased risk of developing T2DM.…”
Section: Introductionmentioning
confidence: 99%